Effectiveness of non-technical skills training in intensive care units: a systematic review - Pimenta, Isac Davidson Santiago Fernandes; Mata, Ádala Nayana de Sousa; Bezerra, Isaac Newton Machado; de Araújo, Rícia Medeiros Palmeira; Santana, Jorge Lucas Alves; Capucho, Helaine Carneiro; de Souza-Oliveira, Adriana Catarina; Echevarría-Pérez, Paloma; Guillén-Martínez, Daniel; Piuvezam, Grasiela (BMC medical education, 2025)
Background Non-technical skills (NTS) are social, cognitive and psychological skills that are related to safety and efficiency in the healthcare process. These skills have an important role in the intensive care once are closely related to the occurrence of safety incidents. This study aims to examine the effectiveness of NTS training programs in intensive care units using Kirkpatrick’s evaluation model, encompassing reaction, learning, behaviors, and organizational results. Method We conduct a systematic review of original articles in the following databases: Pubmed (Medline), Scopus, Web of Science, Science Direct, CINHAL (EBSCOhost), EMBASE (Elsevier), and PsycINFO. We include randomized clinical trials, quasi-experimental studies, and those employing a before-and-after design. Two pairs of independent reviewers selected and assessed the studies, with any discrepancies resolved by a fifth reviewer. Risk of bias and quality assessments were performed using Cochrane Risk of Bias 2, Risk of Bias in Non- randomized Studies of Interventions and Quality Assessment Tool developed by the National Heart, Lung, and Blood Institute. Results Fourteen studies were included, with 11 employing a before-and-after design. Overall study quality was assessed as moderate or low. Simulation training was the main teaching strategy of the training programs. In the reaction dimension, participants (502 participants) generally perceived the training programs as beneficial, despite variations in teaching strategies. Only two studies evaluated the impact on the learning dimension (383 participants), with small improvements. A positive correlation was identified between the adoption of NTS training programs and improved teamwork (413 participants and 183 direct observations), situational awareness (444 participants and 183 direct observations), leadership (183 participants and 155 direct observations), and communication (183 participants and 1141 direct observations). Organizational results showed no significant changes in patient safety culture, length of stay or mortality rates (15776 patients). However, there was a reduction in response time to cardiopulmonary resuscitation and lower adjusted mortality and complications rates (7721 patients). Conclusion The implementation of NTS training programs in intensive care units may improve healthcare professionals’ performance, especially in teamwork, situational awareness and communication. However, it is necessary to conduct more robust experimental studies to establish causality and explore broader impacts on patient safety and costs. Registration CRD42021244769.